Evaluation of herbal extracts for antibacterial activity against Staphylococcus aureus and Klebsiella pneumoniae micro-organisms - SAHNI, Y P; GAUTAM, VIDHI; SHUKLA, DEEPTI (The Indian Journal of Animal Sciences, 2011)
The MIC of aqueous extract of Boerhaavi diffusa, Eclipta alba and Withania somnifera was recorded as 62. 5 and 50 mg, respectively, against Staphylococcus aureas bacteria. The alcoholic extracts of Boerhaavia diffusa, EcliptCl alba and Withania somnifera were more effective against S. aureus with MIC of 50, 12.5, 21.87 mg, respectively. However, aqueous and alcoholic extracts ofBoerhaavia dfffu.sa, Eclipta alba and Withania somnifera were resistant against Klebsiella pneumoniae. Â